Programa de Acção Social Produtiva (PASP) - Documento Base - INAS - Instituto Nacional de Acção Social (Ministério da Mulher e da Acção Social, República de Moçambique, 2012)
O presente documento surge assim como um instrumento de operacionalização do PASP visando clarificar as intervenções deste programa que é mais uma contribuição da segurança social básica para os esforços do Governo no combate à pobreza, alinhando-se com outras intervenções em curso, como por exemplo, o Programa Estratégico de Redução da Pobreza Urbana (PERPU), o Fundo de Desenvolvimento Distrital (FDD) e o Programa Nacional de insumos Agrícolas. O PASP procura contribuir para a superação da insegurança alimentar crónica agravada pelos choques e riscos estruturais e impactos das mudanças ambientais, como as secas, desemprego, permitindo que os agregados familiares abrangidos tenham estabilidade económica e social. O PASP toma como alvo de intervenção os Agregados Familiares (AF) com pelo menos um elemento com capacidade para o trabalho, enfrentando altos níveis de vulnerabilidade, com prioridade para os agregados chefiados por mulheres, por pessoas com deficiências e com crianças com problemas de desnutrição, que estejam localizados nas zonas urbanas e rurais, a partir do envolvimento destes em trabalhos públicos como principal veículo para a disponibilização de transferências sociais monetárias que lhes permitam estabilizar o seu rendimento e consumo. Os mesmos agregados familiares são encorajados em seguida a se envolverem em iniciativas de geração de rendimentos através de um conjunto de acções enquadradas num processo de preparação social para a graduação. O presente documento desenvolve o modelo de intervenções do PASP, os seus objectivos, componentes, nomeadamente, trabalhos públicos com o uso da mão-de-obra intensiva e apoio ao desenvolvimento de iniciativas de geração de rendimentos, as ligações necessárias entre este. Programa e outros processos no âmbito do combate à pobreza, bem como os mecanismos de implementação, financiamento e os factores críticos de sucesso do Programa.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social